EVALUASI SISTEM MANAJEMEN PARKIR KENDARAAN BUS DI TERMINAL DARURAT LEBAK BULUS - Lutfa Riska Syifa’ Nur Bintang; Fatmawati Oemar (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2022)
Terminal is an infrastructure supporting activities in providing services to the user. The Lebak Bulus Terminal was previously a Class A terminal which is currently operating on a regular basis emergency and relocated on an area of 500 m 2 which is a grant land. Based on From this background, this research was born with the aim of knowing the need for parking space optimal, development that can be done. As well as the best policies. In this study the calculations used include: static capacity for determination parking space requirements, dynamic capacity to determine the terminal's ability to serve bus vehicle parking, parking duration to see how long a vehicle arrives leaving the terminal, parking volume to find out the total number of vehicles that are in a place, index and parking turn over to determine the percentage level of vehicles against time. Based on the results of these calculations, the current condition of the terminal is 496.5m2 2 with a static capacity of 5 SRP, to accommodate as many as 32 vehicles. Based on calculation of theZ formula for static capacity of 8 SRP with a dynamic capacity of 61 vehicles. Whereas parking space needs in 2025 with a growth rate of 34.1%, Capacity requirements Static as much as 24 SRP for 175 vehicles. And the required parking area is 1,020m2. Terminal development that can be done is with the concept of a vertical building for the Terminal Lebak Bulus.